ASSESSMENT OF SUSTAINABILITY AND EFFECTIVENESS OF INNOVATIVE DEVELOPMENT OF ECONOMIC AGENTS OF THE RUSSIAN ARCTIC - Nikolay E. Egorov; Alexander V. Babkin; Ivan A. Babkin; Alexey B. Martynushkin (Север и рынок: формирование экономического порядка, 2022)
Based on the selected key indicators in the innovation sphere, an integral rating assessment of the level of innovative development (IRR) of the Arctic Zone of the Russian Federation for the period 2015–2019 was carried out and their innovative profiles were constructed, allowing to identify the strengths and weaknesses of the innovative potential of the subjects. On the basis of comparative ratings, the sufficiency of using the number of indicators for calculations and analysis of the obtained research results is justified. The rating assessment showed the leading position of the Krasnoyarsk Territory, the outsiders of the ranking include the Chukotka and Nenets Autonomous Okrugs. The authors propose a method for determining the level of sustainability of the IRR, which is calculated according to the consolidated integral index of innovative development of the region. The proposed methodological approach is based on the use of the coefficient of variation, well-known in the field of probability theory and statistics, and can be used to assess the innovation sustainability not only of regions, but also for other sectors of the economy and social sphere with corresponding changes in the system of indicators reflecting their production and economic activities. On the basis of input and output parameters, a rating of the effectiveness of innovative activity of the regions is compiled and the possibility of predictive assessments of its level for the future is shown. It is noted that in addition to the regional authorities, the results of the study can be used by various economic and social actors to monitor and forecast innovative development, as well as to adjust the existing regulatory documents in the field of innovation policy.